1986
DOI: 10.1203/00006450-198606000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone Opposes Some Glucocorticoid Effects on Glycogen Content and Lipid Synthesis in Developing Fetal Rat Lung

Abstract: ABSTRACT. Because of current interest in use of a com-used prophylactically to accelerate fetal lung maturation and bination of glucocorticoid and thyroid hormones for pre-prevent RDS in human newborns (2, 3) and in at least one vention of respiratory distress syndrome we examined the clinical study (4) thyroxine was also reported to be effective in effects of dexamethasone and triiodothyronine (T3), alone this regard. However, the findings in a recent multicenter study and in combination, on glycogen content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 32 publications
4
23
0
Order By: Relevance
“…In this cell culture system, however, there is a coordinated induction of lamellar body constituents (SP-B, -C, and phospholipids) and ABCA3 of the limiting membrane, further supporting a role for ABCA3 in lamellar body genesis. These findings are in agreement with earlier studies in other systems that have shown temporal correlations between developmental increases in various enzymes involved in synthesis of fatty acids and surfactant proteins (55)(56)(57)(58)(59) and also demonstrated the glucocorticoid-dependent appearance of lamellar bodies and mRNAs of surfactant proteins (60,61). Numerous other studies have also shown surfactant phospholipid (49,50,53,62) and protein (50,51,60,63) production is developmentally regulated during gestation and reaches maximal levels prior to birth.…”
Section: Discussionsupporting
confidence: 83%
“…In this cell culture system, however, there is a coordinated induction of lamellar body constituents (SP-B, -C, and phospholipids) and ABCA3 of the limiting membrane, further supporting a role for ABCA3 in lamellar body genesis. These findings are in agreement with earlier studies in other systems that have shown temporal correlations between developmental increases in various enzymes involved in synthesis of fatty acids and surfactant proteins (55)(56)(57)(58)(59) and also demonstrated the glucocorticoid-dependent appearance of lamellar bodies and mRNAs of surfactant proteins (60,61). Numerous other studies have also shown surfactant phospholipid (49,50,53,62) and protein (50,51,60,63) production is developmentally regulated during gestation and reaches maximal levels prior to birth.…”
Section: Discussionsupporting
confidence: 83%
“…It is clear that the administered hormones have variable responses at the different stages of incubation, as is also the case in the fetal sheep (22) and rat (47). We speculate that this effect may be the result of the natural variation in maturation rates of different receptors and changes in the rates of PL production throughout incubation.…”
Section: Development Of Surfactant Pls In Crocodilesmentioning
confidence: 75%
“…Each trachea was then ligated to maintain the lungs in standardized inflation during fixation. Midcoronal paraffin sections (8 pm) stained with hematoxylin and eosin were studied stercologically with a Nikon Diaphot inverted microscope (Nikon, Garden City, NY) equipped with a 10x objective 526 SUEN ET .4L. with lung maturation (38). Among the C D H rats, the mean lung at the dose of 0.25 mg/kg on d 18.5 and 19.5, only E T l gene glycogen concentrations were significantly decreased by antenatal expression (Fig.…”
Section: Westbury Ny) On Ice After Adding 19 Volumes Of Distilled Watermentioning
confidence: 99%